Comment on “Unlocking the therapeutic potential of microalgal astaxanthin a super antioxidant in oral cancer and associated ailments” - Peng-Yu Lai; Dan-Ni Liu (Oral Oncology Reports)
Microalgae are a class of unicellular organisms capable of photosynthesis and are widely distributed in marine, freshwater, and other ecosystems, are rich in polyunsaturated fatty acids (PUFAs), astaxanthin, and β-carotene. Their unique properties, including anti-inflammatory, antioxidant, and anticancer effects, make them attractive for medical applications. In addition to using microalgae extracts for the treatment of oral cancer, whole microalgae cells can be directly employed in the therapeutic process, paving the way for “photosynthetic therapy” in humans. Microalgae hold promise for innovative medical treatments, particularly in oral oncology and tissue regeneration.